Analysis of Students' Problem-Solving Ability through Coastal Culture–Based Realistic Mathematics Learning - Carolina Selfisina Ayal; Anderson Leonardo Palinussa (Journal of Innovation in Educational and Cultural Research, 2026)
This study investigates students' mathematical problem-solving ability through Coastal Culture–Based Realistic Mathematics Education (RME). Problem-solving is a critical 21st-century competency and a central goal of mathematics education; however, conventional instruction often fails to connect mathematical concepts with students' real-life contexts. The objective of this study is to analyze the effect of RME on students' mathematical problem-solving abilities after they receive realistic learning based on coastal potential. A quasi-experimental design with a pretest–posttest control group was employed, involving 120 eighth-grade students from three junior high schools in West Seram Regency. The experimental group received coastal potential–based RME instruction, while the control group experienced conventional learning. Data were analyzed using descriptive statistics, normality and homogeneity tests, independent t-tests, and ANOVA. The results revealed a significant difference in improvement between the experimental and control groups (p 0.05), with the experimental group achieving a moderate and effective N-gain (67.8%), compared to the ineffective gain in the control group (20.8%). The findings conclude that coastal culture–based RME is more effective in enhancing students' problem-solving abilities than conventional methods. This study contributes to mathematics education by integrating local cultural context into RME, providing an innovative framework for contextualized learning in secondary education.